05 SUSTAINED EXPRESSION OF GLUCOCORTICOID-INDUCED LEUCINE ZIPPER (GILZ) MARKS A POPULATION OF FUNCTIONALLY IMMATURE INTESTINAL REGULATORY T CELLS IN FEMALE CROHN'S DISEASE PATIENTS. (7th February 2019) - Goodman, Wendy; Bedoyan, Sarah; Havran, Hannah; De Salvo, Carlo; Pizarro, Theresa
Abstract: Background: In addition to its classic roles in sexual development and function, estrogen ("E2") is an important immune regulator. The impact of E2 in a given cell is determined by the relative contribution of signaling downstream of two ligand-activated nuclear receptors, estrogen receptors alpha and beta (ERa, ERb), with ERb generally mediating anti-inflammatory effects. Altered ER signaling likely contributes to the female sex bias observed for many autoimmune diseases including Crohn's disease (CD). We observed reduced ERb expression in inflamed mucosal tissues and peripheral blood T cells from female CD patients, suggesting that reductions in ERb signaling may promote chronic intestinal inflammation in females. Methods: To investigate the contribution of ERb signaling in an experimental ileitis model, we backcrossed mice lacking ERb (ERb-KO) onto SAMP/YitFc (SAMP) mice, generating SAMP-ERb-KO mice lacking global ERb expression. CD patient T cells were FACS-sorted from heparinized peripheral blood from adult volunteers naïve to biologic therapies and corticosteroids. Results: SAMP-ERb-KO mice demonstrated a female-specific exacerbation of ileitis, in which ileal inflammation developed at an earlier age and to a more severe extent in SAMP-ERb-KO female mice compared to SAMP-ERb-KO male mice or to native SAMP mice expressing ERb. Flow cytometric analysis of CD4+ T cells isolated from the mesenteric lymph node (MLN) revealed a decrease in regulatory T cell (Treg) frequency and suppressive function in SAMP-ERb-KO female mice, with a significant reduction in peripherally-induced Tregs. Next-generation RNA sequencing of intestinal Tregs from SAMP-ERb-KO male versus female mice revealed sex-based differences in the expression of several target genes. The most significant of these was Tsc22d3 (GILZ), a glucocorticoid-induced leucine zipper gene showing five-fold upregulation in Tregs from SAMP-ERb-KO female mice. We observed similar overexpression of GILZ in Tregs isolated from female CD patients. GILZ is an E2-regulated gene that affects several aspects of T cell function including peripheral Treg differentiation and Th17 responses. GILZ expression has not been previously observed in mature Tregs. Our data reveal that sustained expression of GILZ in SAMP-ERb-KO female Tregs correlates with impaired suppressive function, suggesting that ERb-mediated negative regulation of GILZ in peripheral Tregs represents an important immunoregulatory circuit contributing to peripheral Treg homeostasis. Conclusions: We show that female SAMP-ERb-KO mice and female CD patients exhibit reductions in anti-inflammatory ERb expression, leading to sustained expression of GILZ among peripheral Tregs. Sustained GILZ expression marks a population of immature, functionally insufficient Tregs that may contribute to the enhanced inflammation frequently observed in female CD patients.